Beyond the double-edged sword of cultural diversity in teams: Progress, critique, and next steps - Minbaeva, Dana; Fitzsimmons, Stacey; Brewster, Chris (Journal of International Business Studies, 2021)
Ten years ago, Stahl et al. (J Int Bus Stud 41:690–709, 2010) performed a meta-analysis of the literature on cultural diversity and team performance, aiming to improve our understanding of “the mechanisms and contextual conditions under which cultural diversity affects team processes” (p. 691). State-of-the-art studies still echo the article’s conclusion about the ‘double-edged sword’ of cultural diversity, referring to the trade-off between process losses and gains. In this commentary, we assess progress within the past decade on our understanding of this double-edged sword. We argue that in terms of adding new insights, IB, as a field, has made substantial progress with respect to understanding diversity within teams, moderate progress with respect to input-process-output logic, and minimal progress with respect to definitions of cultural diversity. Our recommendations for moving beyond the double-edged sword metaphor in the next decade include shifting focus from cultural diversity per se to how it is managed, moving away from simplicity towards unfolding complexity, and expanding diversity categories beyond culture, and mechanisms beyond knowledge or information.